SAT0121 Serum β-D-Glucan-Positive Pneumocystis Jirovecii-Polymerase Chain Reaction-Negative Acute Bilateral Lung Injury is a Clinical Condition Specific to Rheumatoid Arthritis Among Systemic Autoimmune Diseases. (9th June 2015) - Yokosuka, K.; Shimada, K.; Nunokawa, T.; Sugii, S.
Abstract : Background: Pneumocystis pneumonia (PCP) is an opportunistic infectious disease which sometimes occurs during immunosuppressive therapy against systemic autoimmune diseases (SIDs), including rheumatoid arthritis (RA). PCP in SIDs patients manifests as acute bilateral lung injury. Serum β-D-glucan (bDG), which serves as a marker for the fungal component of P. jirovecii, and the polymerase chain reaction test for P. jirovecii (PC-PCR) are reportedly useful tools for diagnosing PCP. On the other hand, SIDs themselves, including RA, can also cause lung injuries difficult to distinguish from the symptoms of PCP. However, given the high mortality rate among SIDs patients suffering from PCP, therapeutic intervention against multiple possible causes of lung injury under the provisional diagnosis of "clinical PCP" is imperative. Objectives: To compare the characteristics of "clinical PCP" in RA patients with those in non-RA SIDs patients in order to elucidate the pathogenesis of "clinical PCP" in SIDs patients. Methods: Medical records of all SIDs patients who were admitted to our hospital due to respiratory failure, and whose sputum and/or bronchoalveolar lavage fluid were tested using PC-PCR between 2006 and 2013, were retrospectively reviewed. PC-PCR was performed with the single-primer-pair PCR test as reported 1 . Patients satisfying the criteria below were identified as having "clinical PCP": (1) positive serum bDG, (2) pulmonary computed tomography findings compatible with PCP, and (3) successful antipneumocystic treatment with sulfamethoxazole/trimethoprim, or pentamidine. Patients who had already undergone methylprednisolone pulse therapy, or had completed sufficient antibiotic treatment against bacterial pneumonia were excluded. Results: A total of 35 cases of "clinical PCP" with a history of SIDs were identified from the medical records. Of these, all 9 patients who were negative for PC-PCR suffered from RA. Among the 35 cases, RA had been diagnosed in 25 and a non-RA SIDs had been diagnosed in the remaining 10. Among the RA patients, the lymphocyte count, MTX dosage, proportion of MTX use, and disease duration were significantly greater, while glucocorticoid dosage was significantly lower, than in the non-RA patients. Serum bDG levels tended to be lower in RA. When RA cases were divided into two groups on the basis of the PC-PCR results, the PCR-positive RA group presented intermediate characteristics between the non-RA and the PCR-negative RA group (Figure 1 ). Details of the immunosuppressive therapy administered to each patient are shown in Figure 2 . MTX was administered to all patients with negative PC-PCR results, with the exception of one patient who received only high-dose prednisolone. All patients with positive PC-PCR results were administered a glucocorticoid, TNF inhibitor, or an immunosuppressant other than MTX. No patient who was administered MTX alone reported positive PC-PCR tests. Conclusions: bDG-positive, PC-PCR-negative, acute, bilateral lung injury is a clinical condition specific to RA among the SIDs. P. jirovecii infection, MTX, and RA itself may pose the risk of pulmonary injury not exclusively but in additive ways. References: Lancet 1990;336:451 Disclosure of Interest: None declared